2009
DOI: 10.1007/s10334-009-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of polyunsaturated omega-6 fatty acid in human malignant prostate tissue by 1D and 2D high-resolution magic angle spinning NMR spectroscopy

Abstract: It is possible to detect PUFAs in prostate tissues using our NMR-based spectroscopic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
4
23
0
Order By: Relevance
“…1B; 100% malignant, Fig. 1C; corresponding morphological pictures are presented on the left side of each NMR spectrum), as indicated, including: lactate (1.33 ppm), alanine (1.48 and 3.78 ppm), glutamate (2.05, 2.15, and 2.35 ppm), glutamine (2.14 and 2.47 ppm), citrate (2.55 and 2.65 ppm), diallylic protons (omega-6,20 2.80 ppm), creatine (3.02 and 3.94 ppm), polyamines (3.05–3.15 ppm), choline (3.20 ppm), glycerophosphorylcholine + phosphorylcholine (GPCho + PCho, 3.22 ppm), taurine (3.25 and 3.46 ppm), myo-inositol (3.29 and 3.52–3.62 ppm) and scyllo-inositol (3.35 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…1B; 100% malignant, Fig. 1C; corresponding morphological pictures are presented on the left side of each NMR spectrum), as indicated, including: lactate (1.33 ppm), alanine (1.48 and 3.78 ppm), glutamate (2.05, 2.15, and 2.35 ppm), glutamine (2.14 and 2.47 ppm), citrate (2.55 and 2.65 ppm), diallylic protons (omega-6,20 2.80 ppm), creatine (3.02 and 3.94 ppm), polyamines (3.05–3.15 ppm), choline (3.20 ppm), glycerophosphorylcholine + phosphorylcholine (GPCho + PCho, 3.22 ppm), taurine (3.25 and 3.46 ppm), myo-inositol (3.29 and 3.52–3.62 ppm) and scyllo-inositol (3.35 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Several metabolomics studies performed in PCa tissue revealed an increase of choline levels in PCa samples, which indicates alterations in phospholipid membrane synthesis and hydrolysis (Table 4) [84], [86], [88], [89], [92], [93], [94]. Because this elevated proliferation rate also increases cell energy requirements, PCa samples also have alterations in lipid metabolism (as lipids may be used by the cells to produce energy) (Table 4) [49], [95].…”
Section: Altered Metabolism Of Pca Cellsmentioning
confidence: 99%
“…4. Other metabolites that have been reported to be markers for PCa vs. normal and BPH prostate tissues include sarcosine 31 , lactate 21 , taurine 30 , glutamate 30 , lysine 29 , myo-inositol 27 , and omega-6-fatty acids 72 , all of which may be present at significantly higher levels in PCa tissues.…”
Section: Metabolism In Prostate Cancer Cellsmentioning
confidence: 99%